Agricultural education in Rio Grande do Norte (1908-1930) (Research, Society and Development, 2018)
This work aims to understand the actions of the State of Rio Grande do Norte regarding agricultural education in the years 1908 to 1930. For this, we began the process of mapping and documentary analysis of the messages of the governors of Rio Grande do Norte, which constitute As sources for this investigation. The time cut is justified by the reform of primary education that reorganized education in the state in 1908, and the moment of political change since the 1930s, as well as the lack of documentation in the years after the 1930s about Of agricultural education. From this perspective, we seek to answer the following questions: What are the characteristics of professional education in the First Republic in Rio Grande do Norte? What are the actions of the State for the development of agricultural education? What was needed to create an agricultural school? The theoretical framework is based on the conception of professional education according to Manfredi (2003) and the dimension of political history according to René Remond (2003). The results show us the process of creating agricultural schools and demonstration fields, as well as the processes of analysis and determination of the need to create these establishments in the State, the preparation and apparatus required for the operation as acquisition of materials, farms and Specialized human resources for the implementation and operation of educational establishments.